2015
DOI: 10.1177/0305735615585398
|View full text |Cite
|
Sign up to set email alerts
|

The art of sight-reading: Influence of practice, playing tempo, complexity and cognitive skills on the eye–hand span in pianists

Abstract: Sight-reading is a skill required by musicians when they perform sheet music unknown to them. It demands sequential anticipatory eye fixation of notes immediately followed by motor execution. The distance between eye (fixation of a note) and hand position (tapping the corresponding key) is called eye-hand span (EHS). The aim of our study was to investigate the influence of practice, playing tempo and complexity of the music on the size of the EHS, as well as its relation to performance and cognitive skills (sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(115 citation statements)
references
References 18 publications
5
107
2
1
Order By: Relevance
“…However, a question arises when comparing two studies that directly analysed the correlation between the EHS and sight-reading proficiency 9,10 . Interestingly, the two studies showed contrasting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a question arises when comparing two studies that directly analysed the correlation between the EHS and sight-reading proficiency 9,10 . Interestingly, the two studies showed contrasting results.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between the EHS and sight-reading accuracy was strongly positive in the study conducted by Sloboda 9 but almost absent in the study conducted by Rosemann et al . 10 . What is the cause of this discrepancy?…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies on sight-reading measured eye movements while the pianists were sight-reading or while they read the score as they played (e.g., Goolsby, 1994 ; Waters et al, 1997 ; Drai-Zerbib et al, 2012 ; Rosemann et al, 2015 ). Goolsby (1994) reported that better sight-readers did not fixate on all the notes, but crossed lines and phrase boundaries, while less proficient sight-readers tended to fixate on individual notes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the eye-hand span is affected by playing tempo and music complexity ( Sloboda, 1984 ; Rosemann et al, 2015 ). In addition, pianists estimate forthcoming notes by using their knowledge of common phrases and chord progression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, musicians have to make sense of the complex symbolic system and select what to target their gaze at, as well as when and for how long, in order to perform successfully while operating within the given temporal framework. We know that musicians manage this by maintaining their gaze slightly ahead of the current point of performance, and with the help of this buffer (typically of perhaps around 1-2 seconds [Furneaux & Land, 1999;Penttinen, et al, 2015;Huovinen, Ylitalo, & Puurtinen, 2018;Rosemann, Altenmüller, & Fahle, 2016; see Video 1]), the performer prepares for the upcoming motoric responses. The gaze may typically tend to remain very close to the performed notes (Truitt et al, 1997;Penttinen, et al, 2015), but instead of a steady "looking ahead", at least for skilled music readers, the reading may also consist (mainly or in part) of rapid back and forth eye movements (Goolsby, 1994;cf.…”
Section: Music Reading Is All About the Use Of Timementioning
confidence: 99%